Biosynthetic Mechanisms and Biological Significance of Glycerol Phosphate-Containing Glycan in Mammals - Rieko Imae (MDPI AG, 2021)
Bacteria contain glycerol phosphate (GroP)-containing glycans, which are important constituents of cell-surface glycopolymers such as the teichoic acids of Gram-positive bacterial cell walls. These glycopolymers comprising GroP play crucial roles in bacterial physiology and virulence. Recently, the first identification of a GroP-containing glycan in mammals was reported as a variant form of O-mannosyl glycan on α-dystroglycan (α-DG). However, the biological significance of such GroP modification remains largely unknown. In this review, we provide an overview of this new discovery of GroP-containing glycan in mammals and then outline the recent progress in elucidating the biosynthetic mechanisms of GroP-containing glycans on α-DG. In addition, we discuss the potential biological role of GroP modification along with the challenges and prospects for further research. The progress in this newly identified glycan modification will provide insights into the phylogenetic implications of glycan.